Padronização da análise dos produtos da PCR/RFLP que amplifica os genes Ribossomal Internal transcribed spacer (ITS) e Glucose-6- phosphate dehydrogenase (G6PD) para identificação de Leishmania spp. em gel de poliacrilamida - Marques, Cálita Pollyanna (2017)
American Cutaneous Leishmaniasis (LTA) is caused by protozoa of the genus Leishmania and it attacks the skin and/or mucous membranes. It is an endemic zoonosis in Brazil being notified in all the Regions. There is a relation between the species of parasite and the clinical manifestations, contributing to the diagnostic complexity, which up to the present, did not exist species-specific diagnosis. In the present work, the proposal was to standardize the analysis of the PCR/RFLP products to the ITS and G6PD genes in polyacrylamide gel. In order to standardize PCR/RFLP analysis on the ITS and G6PD genes, DNA from the reference Leishmania spp. Sample was used and 5%, 6%, 7% 8% and 10% polyacrylamide were tested. The protocol design considered the size of the amplicons generated by the PCR / RFLP, correlating the concentration of the polyacrylamide. To standardize the electrophoresis time the migration of the dyes used in the DNA sample buffer was monitored. To validate the technique, we selected 521 samples from Tocantins patients fixed on slides and 43 samples of parasite isolates stored in Leishbank. The samples from the patients from Tocantins were analyzed by PCR/RFLP to the kDNA and were selected to those positive for the validation. The concentration of the matrix for analysis of the PCR and RFLP products to the ITS gene was standardized in 6% and 8%, respectively, and distinguished the species L. (L.) amazonensis, but the species L. (V.) braziliensis, L. (V.) guyanensis and L. (V.) lainsoni were not distinguished among themselves, occurring the same between L. (V.) naiffi and L. (V.) shawi. The concentration of the matrix for analysis of the PCR products to the G6PD gene was standardized in 6% and distinguished L. (V.) braziliensis from the others. The validation of the polyacrylamide gel analysis of the PCR products to the ITS target from samples of patients fixed in slides was not performed, since of the 256 samples analyzed only 4 amplified. The validation of the analysis of the products of the PCR to the G6PD target in polyacrylamide gel from 48 samples fixed in slides characterized 81% as L. (V.) braziliensis and, characterized 63% of the isolates of parasites as L. (V.) braziliensis. The PCR/RFLP analyzes performed to discriminate Leishmania spp. are complementary and thus contribute to the species-specific diagnosis of LTA.